Note on the Rate and Energy Efficiency Limits for Additive Manufacturing. (9th October 2017) - Gutowski, Timothy; Jiang, Sheng; Cooper, Daniel; Corman, Gero; Hausmann, Michael; Manson, Jan‐Anders; Schudeleit, Timo; Wegener, Konrad; Sabelle, Matias; Ramos‐Grez, Jorge; Sekulic, Dusan P.
Summary: We review the process rates and energy intensities of various additive processing technologies and focus on recent progress in improving these metrics for laser powder bed fusion processing of metals, and filament and pellet extrusion processing of polymers and composites. Over the last decade, observed progress in raw build rates has been quite substantial, with laser metal processes improving by about 1 order of magnitude, and polymer extrusion processes by more than 2 orders of magnitude. We develop simple heat transfer models that explain these improvements, point to other possible strategies for improvement, and highlight rate limits. We observe a pattern in laser metal technologies that mimics the development of machine tools; an efficiency plateau, where faster rates require more power with no change in energy nor rate efficiency.